1992
DOI: 10.1007/bf00156915
|View full text |Cite
|
Sign up to set email alerts
|

Adding a temporal dimension to a logic system

Abstract: We introduce a methodology whereby an arbitrary logic system L can be enriched with temporal features to create a new system T(L). The new system is constructed by combining L with a pure propositional temporal logic T (such as linear temporal logic with "Since" and "Until") in a special way. We refer to this method as "adding a temporal dimension to L" or ju st"temporalising L". We show that the logic system T(L) preserves several properties of the original temporal logic like soundness, completeness, decidab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 14 publications
(13 reference statements)
0
106
0
2
Order By: Relevance
“…Based on the perspective put forward in (Finger and Gabbay, 1992), such an executable continuous time temporal modelling approach was introduced: the CTBDI-model, a continuous time extension of the BDI-model. In the processing of the CTBDI-model, a temporal simulation process replaces the inference process, which is usually applied to process the (non-temporalised) logic-based BDI-model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the perspective put forward in (Finger and Gabbay, 1992), such an executable continuous time temporal modelling approach was introduced: the CTBDI-model, a continuous time extension of the BDI-model. In the processing of the CTBDI-model, a temporal simulation process replaces the inference process, which is usually applied to process the (non-temporalised) logic-based BDI-model.…”
Section: Discussionmentioning
confidence: 99%
“…Our temporalised BDI-model follows (Finger and Gabbay, 1992). In short, this approach considers a logic system L, and defines a temporal dimension for L based on time-indexed trajectories T, where a state α t at some time point t is characterised by the (state) properties of L that hold in α t .…”
Section: Temporalised Bdi-modelmentioning
confidence: 99%
See 1 more Smart Citation
“…only appears in the source of unary edges. We now present some examples of signatures for modal logic [1,7], linear-time temporal logic [4,15] and intuitionistic logic [14], useful throughout the paper. Example 2.1 Signature for linear-time temporal logic.…”
Section: Languagementioning
confidence: 99%
“…Having in mind different fields of application, several asymmetric ways of combining logics have been reported in the literature, including temporalization [4], modalization [3], globalization [10], probabilization [2] and quantization [9]. We proposed in [12] importing as a general way of asymmetric combination of logics and showed that it subsumes such asymmetric combination mechanisms.…”
Section: Introductionmentioning
confidence: 99%